Audiovisual stimulus during urodynamics to provoke detrusor overactivity: A randomized trial1. Issue 3 (18th December 2018) - Shaw, Jonathan; Negbenebor, Nicole; Wohlrab, Kyle; Raker, Christine; Sung, Vivian
Abstract : Objective: This study estimated the effect of adding an audiovisual (AV) intervention during urodynamic evaluation (UDE) on increasing detrusor contractions (DO) versus routine UDE testing without AV cues. Methods: A randomized trial was conducted of women with overactive bladder (OAB) undergoing UDE with and without AV intervention. The AV intervention was a 1‐minute video on continuous loop showing common OAB triggers. A continuous running waterfall provided auditory stimulation. The primary outcome was the proportion of patients who had DO on UDE, interpreted by masked clinicians. Secondary outcomes included the number, amplitude, and duration of DO and urinary leakage associated with DO. A sample size of 109 per group was calculated to have 80% power to detect a 20% difference with a significance level of 0.05. Results: In all, 109 women each were randomized to standard UDE and to the AV intervention. There was no difference in the proportion of patients with DO on UDE between the intervention and control groups (35% vs 32%, respectively; P = 0.8). Furthermore, there were no differences between the intervention and control groups in leakage with DO on UDE (24% vs 21%, respectively), mean duration of detrusor contractions (23.9 vs 25.3 s, respectively), or mean maximum detrusor pressure during involuntary contractions (18.1 vs 20.6 cm H2 O, respectively). Clinical severity of OAB symptoms was not associated with the detection of DO or other UDE parameters. Conclusions: Addition of AV intervention during UDE did not increase the finding of detrusor contractions. The relationship between OAB triggers, urge incontinence, and urodynamic findings remains unclear.